The Urgency of Initial Coin Offering Regulations in Indonesia - Ade Rizki Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of carrying out this research is to find out the urgency of regulation of initial coin offerings or ICOs in Indonesia. This writing uses a normative method with an approach using statutory approaches, comparative approaches, and descriptive approaches. Legal materials used are primary, secondary, and tertiary obtained from literature studies. Then it will be analyzed systematically which is carried out by classifying legal materials to facilitate analysis and construction. In this regard, as well as paying attention to the development of crypto assets at this time, it is important for regulators to follow matters related to the development of digital assets. Therefore, further regulation of digital assets is needed in Indonesia, one of which is regarding ICO as a guide in organizing public offerings in the scope of digital assets in Indonesia based on ICO arrangements that have been carried out by America. This can be one of the best practice references in order to provide a regulatory umbrella as well as a technical guidance framework in the practice of ICOs in Indonesia